New PCR Primer Pairs Specific for Cryptococcus neoformans Serotype A or B Prepared on the Basis of Random Amplified Polymorphic DNA Fingerprint Pattern Analyses - Aoki, Francisco Hideo (American Society for Microbiology, 1999)
Thirty-three strains of Cryptococcus neoformans were isolated from clinical specimens, including specimens from AIDS patients in Brazil, and were classified into two serotypes; we detected 31 and 2 strains of serotypes A and B, respectively. Random amplified polymorphic DNA (RAPD) fingerprint pattern analyses of these strains of serotypes A and B showed that the patterns were similar for strains of each serotype when three 10-mer primers were used as the RAPD primers. Comparative studies of the fingerprint patterns of the study isolates with those of the reference strains also showed that the RAPD patterns for strains of each serotype were related and that most of the fingerprint bands existed commonly for all strains of each serotype tested. The common RAPD bands (an approximately 700-bp band for serotype A and an approximately 450-bp band for serotype B) were extracted and the DNA sequences were determined. Using this information, we prepared two and one PCR primer pairs which were expected to be specific for C. neoformans serotypes A and B, respectively. Use of each PCR primer combination thus prepared for serotype A or B was 100% successful in identifying the respective C. neoformans serotypes, including the 33 clinical isolates tested in the present study. Among these combinations, one for serotype A was found to amplify DNA from C. neoformans serotype B as well as serotype A. Serotype B-specific PCR primer pairs amplified DNA from not only serotype B strains but also from serotype C strains. The usefulness of other serotype-specific PCR primers for clinical C. neoformans isolates is discussed.